Thermal warpage analysis of PBGA mounted on PCB during reflow process by FEM and experimental measurement. Issue 3 (27th May 2014) - Xia, Weisheng; Xiao, Ming; Chen, Yihao; Wu, Fengshun; Liu, Zhe; Fu, Hongzhi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the thermal warpage of a plastic ball grid array (PBGA) mounted on a printed circuit board (PCB) during the reflow process. Design/methodology/approach – A thermal-mechanical coupling method that used finite-element method software (ANSYS 13.1) was performed. Meanwhile, a shadow moiré apparatus (TherMoiré PS200) combined with a heating platform was used for the experimental measurement of the warpage of PBGA according to the JEDEC Standard. Findings – The authors found that the temperature profiles taken from the simulated results and experimental measurement are consistent with each other, only with a little and acceptable difference in the maximum temperatures. Furthermore, the maximum warpage measurements during the reflow process are 0.157 mm and 0.149 mm for simulation and experimental measurements, respectively, with a small 5.37 per cent difference. The experimental measurement and simulated results are well correlated. Based on the validated finite element model, two factors, namely, the thickness and dimension of PCB, are explored about their effect on the thermal warpage of PBGA mounted on PCB during the reflow process. Practical implications – The paper provides a thorough parametrical study of the thermal warpage of PBGA mounted on PCB during the reflow process. Originality/value – The findings in this paper illustrate methods of warpage study by combination of thermal-mechanical finite element simulation and experimental measurement, which can provide good guidelines of the PCB design in the perspective of thermal warpage during the reflow process.